Assessing the impacts of COVID-19 on the aquaculture industry in South Africa, using the marine mussel farming sector as a case study - Brown-Webb, Bernadette; Nesamvuni, Azwihangwisi E.; de Bruyn, Melanie; van Niekerk, Johan A.; Pillay, Parsuramen (Technium Social Sciences Journal, 2022)
This study investigated the impacts of COVID-19 on the aquaculture sector in South Africa. The study was conducted on the West Coast of the Western Cape, South Africa. A multiple-case study approach was followed, focusing on the marine mussel farming sub-sector in Saldanha Bay. Semi-structured interviews were conducted with the owners or managers of nine mussel farming enterprises, and with nine representatives of role players with responsibility or experience in aquaculture, agriculture, or enterprise development. The results of the study focussed on the impacts of COVID-19 on the aquaculture sector and role player organizations; COVID-19 support; initiatives for preparation, survival, and rebuilding; factors promoting resilience, survival, and rebuilding; and requirements to survive and rebuild the sector. The main impact on the aquaculture sector was the closure of markets, which led to cascading impacts on all aspects of the value chain. Role players were affected through impacts on programmes, projects, and staff. Various COVID-19 relief schemes were made available however these could not address all the needs of the sector. Enterprises prepare for the pandemic and the future through long term planning. The main factors contributing to resilience were subsidisation from shareholders, having reserve funds and multiple streams of revenue. The most critical requirements to survive and rebuild the sector was financial support and the opening of markets. The study recommends follow up assessments of the aquaculture industry to fully understand and quantify the effects of the prolonged pandemic and provide tailor-made solutions for each sub-sector to stabilise, revive and grow the aquaculture sector in the medium to long term. Aquaculture enterprises that have closed or are at risk of closure should be prioritised first before any investment in new ventures is considered. In addition, the development of an aquaculture industry-based Business Continuity Strategy and the Ocean Economy Master plan should be prioritised to assist enterprises until the pandemic is over, to prepare for normalisation of operations thereafter, and to prepare the sector and individual enterprises to be more resilient in case of future global crises and disasters.